Landscape of informed consent practices and challenges in point‐of‐care clinical trials - Caleigh Propes; Trevan Locke; Rachele Hendricks‐Sturrup (Learning Health Systems, 2025)
Abstract Point‐of‐care trials, an approach to trial design that assesses medical product effectiveness while fully integrating research and care, represent a promising opportunity to generate practically relevant evidence efficiently for priority disease areas. However, this approach presents unique considerations for appropriate and ethical informed consent. As point‐of‐care trials evolve, it will be important to examine informed consent through the lens of their supporting technology, of the clinicians who are responsible for administering it, and of their broader regulatory environment. Steps should be taken to establish ethical standards for point‐of‐care trials that reflect and serve the best interests of patients while reducing administrative burden and complexity. Our commentary describes, overall and through the use of real‐world examples, how this work is vital to ensuring a modern clinical trial enterprise that is patient‐centered and equips patients to make fully informed decisions about their health care.